O JEITINHO ESTRANGEIRO: THE INTERNATIONAL CAPITAL STRATEGIES FOR THE CONTROL OF THE TERRITORY IN BRAZIL - Pereira, Lorena Iza [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2018)
Since the beginning of the 21st century, we have experienced a period of intensification of global interest in land, often titled in the international academy as land grabbing. Although it is a historical process in many countries, there are elements that make it unique today, such as the presence of financial capital, drivers and justifications, which requires new strategies of control by foreign agents. The objective of this article is to discuss the strategies of foreign agribusiness to control the territory in Brazil. To achieve this objective, we use as methodological procedures a dense bibliographical revision, as well as quantitative and qualitative data collection through the Land Struggle Database (DATALUTA). As a result, we can verify different strategies used by companies for access to the territory in Brazil, such as mergers, joint ventures and gaps in legislation, and that there is also an intense debate about a possible liberation of land appropriation by foreign agents.
Keywords: Land foreignization; Control of territory; Land grabbing; Legislation